Gen Z: Keren, Beretika, dan Berbudaya dalam Era Manajemen Modern - Wijaya, Shierli (LPMP Imperium, 2025)
The purpose of the Community Service Activity is to develop ethical and cultural values in students in their lives as preparation for facing the future world of work. Generation Z, born between 1997 and 2012, is present as a group that brings a new spirit to the world of work and social life. Their characteristics of being easily adaptable to technology, loving freedom of expression, and caring about ethical and cultural values, make their role very important in the transformation of today's organizations. The method used in this activity is through lectures and discussions using power point and video learning media so that students can understand the topic being discussed. Then the students were given the opportunity to ask questions and also express their thoughts by dividing into 6 groups, each consisting of 8 people. This activity was held on Wednesday, July 9, 2025 at SMK Atisa Dipamkara with a total of 50 participants. From the results of the pre-test in the form of questions given to 25 students, initially their knowledge of ethics and culture was still lacking. While the results of the post-test showed that the students had improved in their understanding very well.